1980
DOI: 10.1063/1.439115
|View full text |Cite
|
Sign up to set email alerts
|

A threshold photoelectron–photoion coincidence study of the N2O+ dissociation between 15 and 20.5 eV

Abstract: Branching ratios and the kinetic energy released in the various fragmentation channels of energy selected N2O+ (15–20.5 eV) were investigated by the technique of threshold photoelectron–photoion coincidence. Pulsed synchrotron radiation from ACO, Orsay’s storage ring, dispersed by a monochromator, was used as a photon source. Threshold electrons were energy selected on the basis of angular and temporal discrimination against energetic electrons. The energy region below 16.388 eV and the ? state were investigat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
41
1
1

Year Published

1982
1982
1989
1989

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 98 publications
(54 citation statements)
references
References 24 publications
11
41
1
1
Order By: Relevance
“…In their threshold photoelectron-photoion coincidence experiment, Nenner et al [12] do not mention energetic NO + ions below 16.5 eV. This discrepancy could be interpreted by the fact that these NO + ions are produced by dissociative autoionization where the autoionization step does not produce threshold photoelectrons (zero KE electrons).…”
Section: The No + Dissociation Channelmentioning
confidence: 99%
See 4 more Smart Citations
“…In their threshold photoelectron-photoion coincidence experiment, Nenner et al [12] do not mention energetic NO + ions below 16.5 eV. This discrepancy could be interpreted by the fact that these NO + ions are produced by dissociative autoionization where the autoionization step does not produce threshold photoelectrons (zero KE electrons).…”
Section: The No + Dissociation Channelmentioning
confidence: 99%
“…By using the coincidence technique [9][10][11][12] it has been shown that the predissociation of the à 2 Σ + starts from its 1,0,0 level at 16.55 eV. Brehm et al [10] and Nenner et al [12] observed a large amount of kinetic energy release. These authors interpreted the broad energy release distribution, as observed at 16.55 eV, by the superposition of discrete values of kinetic energies corresponding to the formation of NO + (X l Σ + ) in the υ = 0-8 levels.…”
Section: The No + Dissociation Channelmentioning
confidence: 99%
See 3 more Smart Citations